2016
DOI: 10.1038/eye.2016.146
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD59 and CFH polymorphisms with acute anterior uveitis in Chinese population

Abstract: PurposeCD59 complement regulator and complement factor H (CFH) have important roles in complement activation pathways, which are known to affect the development of uveitis. The present study was performed to investigate whether an association exists between CD59 and CFH genetic polymorphisms and acute anterior uveitis (AAU).MethodsA total of 600 individuals (300 patients diagnosed with AAU and 300 healthy controls) were recruited for this case-control study. Five single-nucleotide polymorphisms (SNPs) in CD59 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Of them, variants in the CFH, CFB and CFI involved in the alternative pathway, were identified as genetic risk markers for various uveitis subtypes [16][17][18][19][20]. A recent report from our laboratory also demonstrated that the classical pathway gene, C1INH, as well as the central component of the cascade, C3 gene, may confer either no or limited risk for uveitis susceptibility [21,22]. Overall, our findings together suggest that the alternative pathway as well as the "upstream" cascade of complement system confers major genetic impact on uveitis susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of them, variants in the CFH, CFB and CFI involved in the alternative pathway, were identified as genetic risk markers for various uveitis subtypes [16][17][18][19][20]. A recent report from our laboratory also demonstrated that the classical pathway gene, C1INH, as well as the central component of the cascade, C3 gene, may confer either no or limited risk for uveitis susceptibility [21,22]. Overall, our findings together suggest that the alternative pathway as well as the "upstream" cascade of complement system confers major genetic impact on uveitis susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Our research team have made great efforts in depicting the genetic profile of uveitis and intraocular inflammation regarding complement pathway genes, several genes have been extensively investigated and identified to be associated with many forms of uveitis, these genes included complement factor H (CFH), complement factor B (CFB), complement factor I (CFI), and CD59 [15][16][17][18][19][20]. Meanwhile, we have largely ruled out the involvement of some complement factors in the disease genetics, such as component 1 inhibitor (C1INH), and complement component 3 (C3) [21,22]. Notably, some genetic associations between AU and complement genes were also found in NIPU patients in our study cohort, suggesting that these two uveitis entities shared general genetic background although presenting different clinical phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports described that polymorphisms in CFB and CFH specifically associated with anterior uveitis 9 10 . CFB and CFH are immunological factors involved in the complement cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have reported that immunological factors involved in the complement cascade were associated with AAU, with polymorphisms in complement factors B and H ( CFB ) and ( CFH ), specifically associated with anterior uveitis 9 10 . CFB and CFH are key regulators in the complement pathway, sharing the same binding site for C3b, the larger of two elements formed by the cleavage of complement component 3 (C3) 11.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of CC chemokine ligand (CCL) 2, CCL5, and their receptors have been associated with AAU inflammation severity . Moreover, the influence of genetic polymorphisms on uveitis might depend on HLA‐B27 status . Furthermore, only a few studies have noted the relationship between the immune factors and AAU development.…”
Section: Introductionmentioning
confidence: 99%